Advances, limitations, and prospects of biosensing technology for detecting phytopathogenic bacteria. (June 2022) - Ali, Qurban; Zheng, Hongxia; Rao, Muhammad Junaid; Ali, Mohsin; Hussain, Amjad; Saleem, Muhammad Hamzah; Nehela, Yasser; Sohail, Muhammad Aamir; Ahmed, Agha Mushtaque; Kubar, Kashif Ali; Ali, Shafaqat; Usman, Kamal; et al.
Abstract: Phytopathogenic bacteria cause severe economic losses in agricultural production worldwide. The spread rates, severity, and emerging plant bacterial diseases have become serious threat to the sustainability of food sources and the fruit industry. Detection and diagnosis of plant diseases are imperative in order to manage plant diseases in field conditions, greenhouses, and food storage conditions as well as to maximize agricultural productivity and sustainability. To date, various techniques including, serological, observation-based, and molecular methods have been employed for plant disease detection. These methods are sensitive and specific for genetic identification of bacteria. However, these methods are specific for genetic identification of bacteria. Currently, the innovative biosensor-based disease detection technique is an attractive and promising alternative. A biosensor system involves biological recognition and transducer active receptors based on sensors used in plant-bacteria diagnosis. This system has been broadly used for the rapid diagnosis of plant bacterial pathogens. In the present review, we have discussed the conventional methods of bacterial-disease detection, however, the present review mainly focuses on the applications of different biosensor-based techniques along with point-of-care (POC), robotics, and cell phone-based systems. In addition, we have also discussed the challenges and limitations of these techniques. Graphical abstract: Image 1 Highlights: Early detection of a disease is essential to prevent crop loss. The conventional techniques are sensitive and specific for pathogenic identification. Biosensor-based techniques are innovative and promising alternatives. Biosensor-based systems are attractive and efficient for early detection of pathogen.